Qualitative Content Analysis Related to the Use of Instagram @pertamina as Communication Technology in Responding to the Post-Fire Crisis of the Plumpang Depot in March 2023 - Maria Adeline Cornelius (Ridwan Institute, 2023)
On March 3 2023, a fire occurred at the Pertamina Plumpang Depot, Koja, North Jakarta. Transparency and good communication regarding Pertamina's responsibilities are important steps in maintaining trust and minimizing negative impacts on the company's reputation.Situational Crisis Communication Theory can be applied in managing communication in crisis situations. The Instagram account @pertamina shows empathy and concern in dealing with the crisis caused by this fire. This article aims to analyze the use of Instagram as a crisis response strategy after the Plumpang Depot fire on March 3 2023, with a focus on the content on the @pertamina account. The qualitative content analysis method was used in this research, with the unit of analysis being content on Instagram @pertamina in the post-Plumpang Depot fire period, namely between the 4th and March 8, 2023. Data collection was carried out through observation of content, including uploads, captions on images, and captions on posts, and there were ten pieces of content studied. In this research, it was found that Pertamina used a crisis response strategy model in the form ofdeal response strategy in responding to the crisis that occurred. The @pertamina Instagram account is used as communication technology that becomes a bridge to the public in dealing with crises with consistency and in accordance with community expectations, such as providing compensation, apologizing and showing regret, without trying to prove the truth or alluding that the crisis originates from factors outside the organization's control